A Presumptive Case of Human Rabies: A Rare Survived Case in Rural Ghana - Apanga, Paschal Awingura; Awoonor-Williams, John Koku; Acheampong, Michael; Adam, Matthew Ayamba (Frontiers in Public Health, 2016)
Rabies remains endemic in Ghana and continues to pose a major public health threat to humans and animals with nearly hundred percent (100%) case fatality rate in humans. We report of a presumptive case of human rabies whose survival was a rare occurrence in rural Ghana. Lessons from this case study provides a critically needed focus in helping improve rabies surveillance and case management in Ghana. We report of the survival of a 36 year old man who developed clinical rabies three weeks after he was bitten by his dog while restraining the dog with a chain. Prior to this he did not observe any abnormal or rabid behaviour in the dog. Following the bite, he did not immediately resort to hospital treatment, but rather to traditional application of herbs to the laceration he sustained after the bite. Reason given for not seeking immediate hospital treatment was that the dog was not rabid and lack of funds to seek hospital care. However, he began to show symptoms consistent with rabies virus infection after 10 days and was subsequently rushed to the hospital by relatives. At the hospital, he was administered human immune tetanus immunoglobulin, diazepam, ceftriaxone, paracetamol and intravenous fluids. No rabies vaccine was administered. Six days after commencing treatment patient became well, showed no signs of confused state of mind, hydrophobia nor photophobia. He was discharged home after 13 days of commencing treatment. This study provides insight on a presumptive case of Human rabies case that survived despite non-administration of rabies vaccine during esposure. It also exposes the weaknesses in the health and veterinary systems in rural Ghana regarding rabies surveillance and case management.